2007
DOI: 10.1109/titb.2006.884359
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Touch Interface for Medical Education

Abstract: We present the technical principle and evaluation of a multimodal virtual reality (VR) system for medical education, called a touch simulator. This touch simulator comes with an innovative three-dimensional (3-D) touch sensitive input device. The device comprises a six-axis force-torque sensor connected to a tangible object representing the shape of an anatomical structure. Information related to the point of contact is recorded by the sensor, processed, and audiovisually displayed. The touch simulator provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Panchaphongsaphak et al. [PBR07] also use pressure‐augmented touch but for the purpose of orienting and translating a cutting plane within medical data. Pressure beyond a given threshold was used to translate the slicing plane in the direction of its normal.…”
Section: Survey Of the State Of The Artmentioning
confidence: 99%
“…Panchaphongsaphak et al. [PBR07] also use pressure‐augmented touch but for the purpose of orienting and translating a cutting plane within medical data. Pressure beyond a given threshold was used to translate the slicing plane in the direction of its normal.…”
Section: Survey Of the State Of The Artmentioning
confidence: 99%
“…[15][16][17][18][19] In an effort to diminish neurophobia and improve spatial and 3-dimensional neuroanatomy learning, 3-dimensional strategies have been proposed. 3,[20][21][22] Several studies have shown that 3-dimensional neuroanatomical learning is an effective strategy for increasing neuroanatomical knowledge, motivation and retention of neuroanatomy material. 2,[22][23][24][25][26] Furthermore, participants improved in their knowledge of spatial relations when they were exposed to both physical 11 and virtual [25][26][27] 3-dimensional brain models.…”
mentioning
confidence: 99%
“…Explicit geometrical model reconstruction from various imaging modalities has attracted considerable interests in the literatures. Geometrical augmentation was proposed in a Virtual Reality scheme for surgical planning (3) and other medical applications (4) , such as interactive colonoscopy system (5) . More recently, physical modeling was also incorporated into 3D synthetic object to improve realistic sense during medical training.…”
Section: Introductionmentioning
confidence: 99%